2006
DOI: 10.1007/s00595-006-3274-x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Multiple Small-Bowel Perforations Caused by Cytomegalovirus in a Patient with Malignant Lymphoma: Report of a Case

Abstract: We report the successful management of multiple small-bowel perforations caused by cytomegalovirus (CMV) infection in a 60-year-old man, 1 day after CHOP (cyclophosphamide/doxorubicin/vincristine/prednisone) therapy induction for malignant lymphoma. Emergency laparotomy was performed for perforative peritonitis, but we did not resect the lesions at this time. Instead, we exteriorized the small bowel and then irrigated the peritoneal cavity and intestinal tract. His white blood cell count was low, at 200 cells/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Although there are no reported cases of concurrent amebic enteritis and CMV enteritis during pregnancy, it has been reported that 32% of HIV-infected patients with CMV enteritis also have amebic colitis (18). Although CMV exists in more than half of the healthy adult population, it is usually a latent infection and manifests only in immunocompromised patients (19). However, recent studies have demonstrated active CMV infection due to compensated antiinflammatory response syndrome in non-immunosuppressed ICU patients (20).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no reported cases of concurrent amebic enteritis and CMV enteritis during pregnancy, it has been reported that 32% of HIV-infected patients with CMV enteritis also have amebic colitis (18). Although CMV exists in more than half of the healthy adult population, it is usually a latent infection and manifests only in immunocompromised patients (19). However, recent studies have demonstrated active CMV infection due to compensated antiinflammatory response syndrome in non-immunosuppressed ICU patients (20).…”
Section: Discussionmentioning
confidence: 99%
“…The most common causes of colonic perforations are diverticular disease, ischaemic colitis, faecal impaction, neutropaenic enterocolitis, and opportunistic infections such as cytomegalovirus (CMV) and Candida. Perforations secondary to CMV have also been found in the ileum and jejunum among patients undergoing chemotherapy [72,73]. An erect radiograph of the abdomen shows air below the diaphragm pointing to the pneumoperitoneum.…”
Section: Perforationmentioning
confidence: 99%